Cholangiocarcinoma cell proliferation is enhanced in primary sclerosing cholangitis: A role for IL‐17A. Issue 12 (17th November 2022) - Lieshout, Ruby; Kamp, Eline J. C. A.; Verstegen, Monique M. A.; Doukas, Michail; Dinjens, Winand N. M.; Köten, Kübra; IJzermans, Jan N. M.; Bruno, Marco J.; Peppelenbosch, Maikel P.; van der Laan, Luc J. W.; de Vries, Annemarie C.
Abstract: Primary sclerosing cholangitis (PSC) is a chronic inflammatory disease of the biliary tree and a risk factor for development of cholangiocarcinoma (CCA). The pathogenesis of PSC‐related CCA is largely unclear, although it is assumed that chronic inflammatory environment plays a pivotal role. We aimed to investigate the effect of inflammation‐related cytokines in PSC on the proliferation rate of cancer cells. For this, the proliferation index in PSC‐CCA and sporadic CCA was determined by Ki‐67 immunohistochemistry. The percentage of Ki‐67 positivity in cancer cells was significantly higher in PSC‐CCA than in sporadic CCA (41.3% ± 5.7% vs 25.8% ± 4.1%; P = .038). To assess which cytokines in the inflammatory environment have the potential to stimulate cancer cell proliferation, patient‐derived CCA organoids (CCAOs) were exposed to five cytokines related to PSC (Interleukin (IL)‐1β, IL‐6, IL‐17A, interferon gamma and tumor necrosis factor alpha). Only IL‐17A showed a significant stimulatory effect on cell proliferation in CCAOs, increasing organoid size by 45.9% ± 16.4% ( P < .01) and proliferation rate by 38% ± 16% ( P < .05). IL‐17A immunohistochemistry demonstrated that PSC‐CCA might express more IL‐17A than sporadic CCA. Moreover, correlation analysis in sporadic CCA and PSC‐CCA found a significant correlation between IL‐17A expression and proliferation. In conclusion, tumor cell proliferation is increased in PSC‐CCA cells compared with sporadic CCA cells. IL‐17A increases CCA cell proliferation in vitro and may contribute to the high proliferation rate in PSC‐CCA in situ. Therefore, IL‐17A represents a new potential therapeutic target in (PSC‐)CCA, to be tested in future trials. Abstract : What's new? Primary sclerosing cholangitis (PSC) is a chronic fibrotic inflammatory disease of the biliary tree and a risk factor to the development of cholangiocarcinoma (CCA). Differences between PSC‐related and sporadic CCA are poorly studied. Here, we demonstrate that PSC‐related CCA has a higher proliferative index compared with sporadic CCA. Moreover, we show that inflammatory cytokine IL‐17A is locally expressed in tumor tissue and has a direct proliferation inducing effect on biliary cancer cells cultured as organoids.